New asymmetric bisthiocarbohydrazones and their mixed ligand nickel(II) complexes: Synthesis, characterization, crystal structure, electrochemical-spectroelectrochemical property, antimicrobial and antioxidant activity - KOCA, ATIF; UĞUZ NELİ, ÖZLEM (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
New asymmetric isatin bisthiocarbohydrazone ligands were synthesized by the condensation of 3,5-dibromosalicylaldehyde, 3,5-dichlorosalicylaldehyde and 3-bromo-5-chlorosalicylaldehyde with isatin monothiocarbohydrazone. New mixed ligand Ni(II) complexes were synthesized from these ligands using triphenylphosphine (PPh3) as a secondary ligand. The synthesized ligands and complexes were characterized by elemental analysis, FT-IR, H-1 NMR, UV-Vis spectroscopy and mass spectrometry techniques, along with conductivity measurements. The ligands bind to the Ni(II) ion as ONS donors. The fourth coordination site is completed by the secondary ligand PPh3. The single crystal structures of one ligand and one complex were also resolved by X-ray crystallography. The electrochemical responses of the ligands and their complexes were determined and the results were evaluated to illustrate the influence of the substitution of different groups on the ligands. While the free ligands only give one oxidation peak, two oxidation peaks are observed for the Ni(II) complexes. Complexation of the ligands with the Ni(II) ion considerably affected the in-situ spectroelectrochemical responses of the ligands. Finally, the in vitro antioxidant and antimicrobial activities of the synthesized compounds were determined.
Keywords: Isatin thiocarbohydrazone; Nickel(II); CV; Crystal structure; Antioxidant; COPPER(II) COMPLEXES; ANTIBACTERIAL ACTIVITY; DNA/PROTEIN-BINDING; ORGANOTIN(IV) COMPLEXES; ISATIN DERIVATIVES; NI(II) COMPLEXES; METAL-COMPLEXES; THIOSEMICARBAZONE; THIOCARBOHYDRAZONE; DONOR